PENGARUH TERAPI MUSIK KLASIK MOZART TERHADAP BERAT BADAN PADA BAYI BBLR DI RUANG PERINATOLOGI RUMAH SAKIT WANGAYA - Sumawidayanti, Made Wiwin; Sulisnadewi, NLK; Suntari, NLP Yuni (Coping: Community of Publishing in Nursing; Vol 3 No 3 (2015): JURNAL EDISI SEPTEMBER-DESEMBER 2015, 2015)
Low Birth Weight (LBW) babies have their birth weight less than 2500 grams. It is caused by several factors, including the mother, fetus, and the environment. One of the problems experienced by LBW babies are breastfeeding problems which caused by the poor suction of baby's reflexes. Treatment that can be done to LBW babies consists of pharmacological and non-pharmacological treatment. Therapy classical music of Mozart is one of non-pharmacological treatment. Mozart classical is music that provide peace and healing for its listeners. One of the benefits of classical music of Mozart to LBW babies is helping to improve reflexes suction that will help fulfill the nutrition in low birth weight babies. The purpose of this study is to determine the effects of Mozart music therapy on weight-gaining of LBW infants in Wangaya Perinatology Hospital. Benefits for the nursing profession of this study is expected to be material additional information to enrich nursing midwives especially on children who is related to the use non-pharmacological therapy in order to promote weight-gaining of LBW babies. This research was conducted at room Perinatology Wangaya Hospital on April 13 until May 13, 2015. This research method is quasy experimental with sample treated group consist of 10 people and the control group consist of 10 people. Results from this study after a independent statistical t-test was done showed there’s effect of classical music of Mozart on weight gain in LBW infants p <? (0.003 <0.05).
Keywords: Low Birth Weight Baby (LBW), Mozart Classical Music Therapy